Respiratory and Hemodynamic Changes in Neonates with Hypoxic–Ischemic Encephalopathy during and after Whole-Body Hypothermia - Sheppard, Stephanie Rosenbloom; Desale, Sameer; Abubakar, Kabir (American Journal of Perinatology, 2019)
Objective This study aimed to determine the degree to which whole-body hypothermia (WBH) impacts hemodynamic and respiratory status during hypothermia and the subsequent rewarming period in neonates with hypoxic–ischemic encephalopathy (HIE).Study Design This is a retrospective study reviewing the medical records of infants treated with WBH. Data including oxygenation index (OI), ventilator efficiency index (VEI), fraction of inspired oxygen (FiO2), blood lactate level, heart rate (HR), and mean blood pressure (MBP) were collected from defined time points from the beginning, middle, and end of WBH and then every 2 hours from the beginning of rewarming for 14 hours thereafter. The analysis included 65 infants. Data were analyzed using a piecewise linear regression with a mixed-effect model.Results HR decreased during WBH and significantly increased during rewarming. Lactate level, OI, VEI, FiO2, and MBP all decreased during WBH but showed no significant change during and after rewarming.Conclusion There was a decrease in metabolic demand as measured by oxygen requirement, OI, HR, and MBP during WBH, but only HR increased during rewarming, with no significant change in the other parameters. Some of this effect may be explained by improvement in the respiratory condition over time.
Keywords: whole-body hypothermia; hypoxic–ischemic encephalopathy; hemodynamics; respiratory